Increasing Solubility of Simvastatin Via Salting Form Using Isonicotinamide As Co-Formers - Sopyan, Iyan; Puspa, Inge; Salsabila Hapsari, Raira (Universitas Padjadjaran (Unpad), 2024)
Simvastatin is a drugs used to lower plasma cholesterol. Simvastatin is a class II BCS drug that has low solubility and high permeability. One of the efforts made to increase the solubility of simvastatin is the formation of multicomponent crystals (co-crystals and salts). The purpose of this study was to determine the solubility and dissolution profile of multicomponent crystal simvastatin with the best co-former candidate from the in silico test. Simvastatin-co-former multicomponent crystal were prepared using solvent drop grinding method with a mol ratio of 1:1 ; 1:2 and 2:1. Based on the result of value of binding affinity and ability to form hydrogen bonds, isonicotinamide was chosen as the co-former in this research. Evaluation of multicomponent crystals was carried out by solubility and dissolution tests. The evaluation results showed an increase in the solubility and dissolution of the simvastatin-isocotinamide multicomponent crystal with the highest increase occurring in the simvastatin-isocotinamide multicomponent crystal with a mol ratio of 1:2. Multicomponent crystal characterization was carried out to determine physicochemical characteristics. The results of characterization using infrared spectrophotometry showed a spectrum shift. The results of the Differential Scanning Calorimetry (DSC) analysis show a decrease in the melting point. The results of Powder X-ray diffraction analysis showed that there were differences in the shape of the crystals indicated by the formation of new peaks on the diffractogram. So, it can be concluded that simvastatin-isocotinamide multicomponent crystals are able to increase solubility and dissolution compared to pure simvastatin.